Penanaman Mangrove di Desa Sawapudo, Soropia, Kab. Konawe, Sulawesi Tenggara, sebagai Implementasi SDG’s 4, 8, dan 14 - Baru Sadarun; La Ode Alirman Afu; Fatmawati; Chairun Annisa Aryanti (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Coastal areas have diverse functions for environmental balance through the presence of mangrove forests. Mangroves play a crucial role in maintaining coastal stability. This activity aims to be the starting point of a larger movement in environmental conservation, in line with the implementation of SDG, 4 (Quality Education), 8 (Decent Work and Economic Growth), and 14 (Life Below Water), as well as serving as a platform for education, strengthening economic, and raising awareness about protecting the marine environment. Community involvement in mangrove planting activities is carried out through a participatory approach, where students and local residents are not merely objects but active subjects in every stage of the activity. The mangrove planting method consists of preparation, determining planting distance, and group division. A total of 100 Rhizophora mucronata seedlings were prepared for this community service activity. The team of lecturers, coastal community, and students carried out the planting, as part of a community service program in the Marine Education Park Bintang Samudra, Konawe Regency, Southeast Sulawesi. The mangrove planting activity demonstrated a high level of participation from both the community and students. The entire series of activities represents efforts to support the Sustainable Development Goals (SDGs), focusing on SDG 4 (quality education), SDG 8 (decent work and economic growth), and SDG 14 (Life Below Water) which includes the protection of coastal ecosystems.